Elimination patterns of dimetridazole in egg of laying hens and tissues of broiler after oral administration - Mo, Kaibin; Wei, Chaoqun; Bai, Mingyang; Long, Xiangyang; Liu, Xuezhen; Ding, Huanzhong (Frontiers in Veterinary Science, 2024)
Dimetridazole (DMZ) is a broad-spectrum anti-anaerobic and antiprotozoal drug extensively used for the control of blackhead disease in poultry (especially turkeys). The presence of DMZ and its metabolites in animal food poses potential risks to human health. In this study, we developed a high-performance liquid chromatography tandem mass spectrometry (HPLC/MS-MS) method for the precise detection of DMZ and its metabolite 2-hydroxymethyl-1-methyl-5-nitroimidazole (HMMNI).Our results demonstrate a strong linear relationship (r 2 > 0.99) between the concentrations of DMZ and HMMNI in tissues and egg within the range of 1~100 ng/g. The limits of detection (LOD) were determined to be 0.5 ng/g, with corresponding limits of quantification (LOQ) at 1.0 ng/g. Furthermore, average recoveries in tissues and egg fell within the range of 84.90% to 103.01%, with coefficients of variation below 15% for both intra-day and inter-day analyses. To investigate the residue elimination pattern of DMZ and HMMNI, diets containing 500 mg/kg DMZ were fed to healthy SanHuang chicken and Hy-line Grey laying hens for ten consecutive days.The results indicated that the concentration of HMMNI consistently exceeded that of DMZ during the same period, in both broiler tissues and egg. Sebum showed the slowest elimination of DMZ and HMMNI, becoming undetectable after 168 hours of withdrawal. In egg, residues of both substances peaked on the first day after drug withdrawal, followed by slow elimination with half-lives of 0.45 d for DMZ and 0.66 d for HMMNI.Based on these findings, WT1.4 software was used to calculate a withdrawal time of 11 d for broilers and an egg abandonment period of 14 d after withdrawal for laying hens, providing a scientific basis for the safe and rational use of DMZ in poultry farming.